BODY COMPOSITION IN SEDENTARY ELDERLY WOMEN AND THE CORRELATION BETWEEN ADIPOSE TISSUE AND DEPRESSIVE SYMPTOMS - Holubiac Iulian Ștefan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2021)
Twenty-five sedentary women (52 ± 4.5 years) had their body composition measured using the Tanita MC-780MA, and then completed the Depression Scale of the Center for Epidemiological Studies (CES - D). The purpose of the article was to observe if there are correlations between adipose tissue and the level of depressive symptoms. At the end of the study a positive correlation was also found between depression scale and metabolic age, r = .75, p < .001. A positive correlation was found between depression scale and visceral fat, r = .79, p < .001, and the same was found between depression scale and trunk fat (r = .75, p < .001), right arm fat (r = .82, p < .001), right leg fat (r = 82, p < .001), left leg fat (r = .82, p < .001).